Penerapan Pembelajaran Berdiferensiasi Dalam Kurikulum Merdeka Pada Pembelajaran Mufrada - Ilmi Hijratul Jihad, Nur; Suparmanto, Suparmanto; Lutfil Hakim, Muhammad; Nurul Hidayah, Siti (Journal of Arabic Education and Linguistic, 2023)
This research tries to apply differentiated learning in improving the mastery of mufradat class XI A students at MTs NW Mercapada. Differentiated learning itself is learning based on the Merdeka curriculum. The purpose of this research is to determine the results of implementing differentiated learning in improving students' mastery of mufradat. This research uses a qualitative descriptive method where the researcher is directly involved in the process. Data collection methods are observation, interviews and documentation. Descriptive data analysis techniques in qualitative research are the process of analyzing, describing and summarizing events or phenomena. The results of this research show that differentiated learning is effective in improving students' mastery of mufradat in class IX A MTs NW Mercapada, as well as making learning more fun and varied according to students' interests.